2015
DOI: 10.1590/2446-4740.0524
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of tuberculosis mycobacterium

Abstract: Introduction: According to the Global TB control report of 2013, "Tuberculosis (TB) remains a major global health problem. In 2012, an estimated 8.6 million people developed TB and 1.3 million died from the disease. Two main sputum smear microscopy techniques are used for TB diagnosis: Fluorescence microscopy and conventional microscopy. Fluorescence microscopy is a more expensive diagnostic method because of the high costs of the microscopy unit and its maintenance. Therefore, conventional microscopy is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 13 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Nevertheless, it is time-consuming. Therefore, in Costa Filho et al (2015), a novel method based on image processing techniques is proposed to assist the diagnosis. It contains three steps: image acquisition, segmentation, and post-processing.…”
Section: Segmentation Taskmentioning
confidence: 99%
“…Nevertheless, it is time-consuming. Therefore, in Costa Filho et al (2015), a novel method based on image processing techniques is proposed to assist the diagnosis. It contains three steps: image acquisition, segmentation, and post-processing.…”
Section: Segmentation Taskmentioning
confidence: 99%
“…Several other studies proposing methods of automated detection of AFB on ZN stains evaluated smears. Other than delCarpio et al, and Law et al (who evaluated scans of slides containing the whole section present on the slide whole slide images (WSIs)) [ 4 , 5 ], all the other studies evaluated images captured with cameras (small parts of slides) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The specificity and sensibility varied from study to study as shown in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in the literature, methods have been published to automate the diagnosis of TB. These process a sputum smear microscopy image using a variety of computational techniques: digital image processing [2] and [3]), traditional machine learning algorithms [4] and [5], and shallow neural networks and deep neural networks (such as the convolutional neural networks) [6], [7] and [8].…”
Section: Introductionmentioning
confidence: 99%